2018
DOI: 10.1039/c7py01859b
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-responsive micelles by a one-pot polymerization-induced self-assembly approach

Abstract: Combining a sequential, one-pot RAFT polymerization with the polymerization-induced self-assembly process results in a versatile oxidation-responsive carrier system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 49 publications
0
71
0
4
Order By: Relevance
“…PDT requires O 2 , photosensitizers and laser irradiation with specific wavelength to produce singlet oxygen, which destroys the structure and function of target organelles through oxidative damage, causing apoptosis and necrosis of target cells. 7,8 Zinc phthalocyanine (ZnPc) is one of the widely used third-generation photosensitizer. 9,10 Höpfner et al found that tetratriethyleneoxysulfonyl substituted zinc phthalocyanine (ZnPc) is a promising photosensitizer for photodynamic treatment of esophageal cancer, and the growth inhibition of esophageal adenocarcinoma and squamous carcinoma using ZnPc (1-10 μM) under laser irradiation was >90%.…”
Section: Introductionmentioning
confidence: 99%
“…PDT requires O 2 , photosensitizers and laser irradiation with specific wavelength to produce singlet oxygen, which destroys the structure and function of target organelles through oxidative damage, causing apoptosis and necrosis of target cells. 7,8 Zinc phthalocyanine (ZnPc) is one of the widely used third-generation photosensitizer. 9,10 Höpfner et al found that tetratriethyleneoxysulfonyl substituted zinc phthalocyanine (ZnPc) is a promising photosensitizer for photodynamic treatment of esophageal cancer, and the growth inhibition of esophageal adenocarcinoma and squamous carcinoma using ZnPc (1-10 μM) under laser irradiation was >90%.…”
Section: Introductionmentioning
confidence: 99%
“…In dieser Studie wurde der Zerfall der Partikel – und keine morphologischen Übergänge – beobachtet, ausgelöst durch eine hydrophob‐hydrophile Veränderung der Blockcopolymereigenschaften durch Oxidation der Thioethergruppen . Ebenso zeigten Sobotta et al., dass der cyclische Thioether N ‐Acryloylthiomorpholin in PISA verwendet werden kann, um einen hydrophoben Block zu bilden, der bei Oxidation in ein Sulfoxid mit hoher Löslichkeit in Wasser umgewandelt werden kann, was wiederum zum Zerfall der Partikel führt …”
Section: Steuerung Der Partikelmorphologieunclassified
“…Recently, two groups introduced PISA nanoobjects with a core susceptible to modification upon exposure to reactive oxygen species . In one case, aqueous RAFTPISA of N ‐acryloylthiomorpholine (NATM; Scheme ) was performed in the presence of a poly( N ‐acryloylmorpholine) (PNAM) macroRAFT agent and provided spherical nanoparticles .…”
Section: Reactive Pisa Nanoobjectsmentioning
confidence: 99%
“…Recently, two groups introduced PISA nanoobjects with a core susceptible to modification upon exposure to reactive oxygen species . In one case, aqueous RAFTPISA of N ‐acryloylthiomorpholine (NATM; Scheme ) was performed in the presence of a poly( N ‐acryloylmorpholine) (PNAM) macroRAFT agent and provided spherical nanoparticles . Exposure to hydrogen peroxide led to oxidation of the NATM units—the thioether becomes a sulfoxide—which had the effect of drastically changing the solubility of the polyNATM block, eventually inducing dissociation of the assemblies ( Scheme ).…”
Section: Reactive Pisa Nanoobjectsmentioning
confidence: 99%
See 1 more Smart Citation